2019
DOI: 10.1080/15592324.2019.1573096
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous GABA is quickly metabolized to succinic acid and fed into the plant TCA cycle

Abstract: Exogenous application of γ-aminobutyric acid (GABA) could improve plant tolerance to environmental stresses such as hypoxia, heat, cold, drought, and salt stress. However, the mechanism by which GABA relieves stress is poorly understood. Here, we studied the uptake and metabolism of exogenous GABA in citrus leaves. Leaves were incubated in GABA solutions and the levels of endogenous GABA, succinic acid, and fumaric acid were investigated. Interestingly, the levels of endogenous GABA, succinic acid, and fumaric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 5 publications
4
30
0
1
Order By: Relevance
“…Succinate, the anion of succinic acid, forms part of the tricarboxylic acid (TCA) cycle. The increase in succinic acid levels, combined with the decreased abundance of gamma-aminobutyric acid (GABA), is consistent with these species employing the GABA shunt pathway, which was proposed to act as an additional energy source to support cellular metabolism under stress conditions [47][48][49] .…”
Section: Comparisons Of Primary Metabolic Responses To Nutrient-deficit Stressmentioning
confidence: 74%
“…Succinate, the anion of succinic acid, forms part of the tricarboxylic acid (TCA) cycle. The increase in succinic acid levels, combined with the decreased abundance of gamma-aminobutyric acid (GABA), is consistent with these species employing the GABA shunt pathway, which was proposed to act as an additional energy source to support cellular metabolism under stress conditions [47][48][49] .…”
Section: Comparisons Of Primary Metabolic Responses To Nutrient-deficit Stressmentioning
confidence: 74%
“…In addition, no D 6 -GABA was detected in seedlings 24 h upon incubation for 6 h in 10 mM D 6 -GABA, confirming that it was completely metabolized to succinic acid. Recently, we showed that the levels of GABA and succinic acid were significantly increased in detached citrus leaf after 1 h incubation in 10 mM GABA, indicating that GABA was quickly metabolized to succinic acid [16]. In addition, the level of fumaric acid was significantly increased in citrus leaves after 1 h incubation in 10 mM GABA, indicating that succinic acid was fed into the TCA cycle [16].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, we showed that the levels of GABA and succinic acid were significantly increased in detached citrus leaf after 1 h incubation in 10 mM GABA, indicating that GABA was quickly metabolized to succinic acid [16]. In addition, the level of fumaric acid was significantly increased in citrus leaves after 1 h incubation in 10 mM GABA, indicating that succinic acid was fed into the TCA cycle [16]. Unfortunately, no D 2 -labeled fumaric acid was detected in D 6 -GABA-treated plants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Succinic acid, in turn, promotes energy production through the maintenance of the tricarboxylic acid cycle, often inhibited in stress conditions (Li et al, 2017; Shelp et al, 2017). An exogenous source of GABA was shown to increase the concentration of both endogenous GABA and succinic acid (Hijaz and Killiny, 2019). To summarize, it would seem that homogeneous-hillslope prokaryotic communities reduce ammonia availability and provide less pathogen response mechanisms, and are therefore detrimental to plants, in comparison with the communities of heterogeneous hillslopes.…”
Section: Discussionmentioning
confidence: 99%